2021
DOI: 10.3390/nu13010239
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins and Flavan-3-ols in the Prevention and Treatment of Periodontitis—Immunomodulatory Effects, Animal and Clinical Studies

Abstract: This paper continues the systematic review on proanthocyanidins and flavan-3-ols in the prevention and treatment of periodontal disease and covers the immunomodulatory effects, and animal- and clinical studies, while the other part discussed the direct antibacterial properties. Inflammation as a major response of the periodontal tissues attacked by pathogenic microbes can significantly exacerbate the condition. However, the bidirectional activity of phytochemicals that simultaneously inhibit bacterial prolifer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Although few compounds were studied, these results put focus on structural characteristics that best contribute to the activity of such drugs as TACE inhibitors. The results of simulation studies are consistent with the reported activity of procyanidins, where a procyanidin enriched extract revealed a reduction in TNF-α levels and suppressed the LPS-stimulated inflammatory response in the RAW264.7 cells [54]. Further, this will add to our understanding of the flavonoid structural requirements and the pharmacophores concerned with the receptor-protein complex.…”
Section: Discussionsupporting
confidence: 86%
“…Although few compounds were studied, these results put focus on structural characteristics that best contribute to the activity of such drugs as TACE inhibitors. The results of simulation studies are consistent with the reported activity of procyanidins, where a procyanidin enriched extract revealed a reduction in TNF-α levels and suppressed the LPS-stimulated inflammatory response in the RAW264.7 cells [54]. Further, this will add to our understanding of the flavonoid structural requirements and the pharmacophores concerned with the receptor-protein complex.…”
Section: Discussionsupporting
confidence: 86%
“…It is stronger than other extracts and stimulated fibroblasts proliferation and migration, which may be related to its highest content of resveratrol and the appropriate composition of procyanidins in it. Both resveratrol and procyanidins have proven immunomodulatory, anti-inflammatory, antioxidant, and antibacterial activity, positively influencing the prevention or treatment of periodontal diseases [34][35][36]. These proven effects of compounds that are present in the 25% EtOH extract may have additional benefits in the treatment of wounds where inflammation, oxidation, modulation of signal transmission, and other mechanisms are important parts of a healthy healing process.…”
Section: Total Polyphenols and Tannins Contentmentioning
confidence: 99%
“…The expression of TGF-β1 and activation of H19/SAHH signalling pathway could induce the expression of OCN, RUNX2, and Distal-Less Homeobox 3 (DLX3) then DSPP is elevated. [69][70][71][72][73][74][75][76][77][78][79] DSPP followed by release of calcium (Ca 2+ ) and phosphate (PO4 3-) by PAMAM-CP nanoparticles fragment facilitate PAMAM fixation to the ions to form hydroxyapatite. The increase in extracellular Ca 2+ induces the formation of Dentin matrix protein 1 and its receptor, Glucose regulated protein-78 (DMP1-GRP78) complex and FGF2 expression, then induces interaction between Calcium release-activated calcium channel protein 1(Orai1) and stromal interaction molecule-1 (STIM1) to activate the store-operated Ca 2+ entry (SOCE) signaling pathway.…”
Section: Pa Loaded Pamam-cp Nanoparticles As Pulp Cappingmentioning
confidence: 99%